Treatment, outcome and quality of life after Fournier's gangrene: a multicentre study. (December 2013) - Czymek, R.; Kujath, P.; Bruch, H.‐P.; Pfeiffer, D.; Nebrig, M.; Seehofer, D.; Guckelberger, O.
Abstract Aim The object of this study was to describe the course of Fournier's gangrene and assess quality of life in a group of affected patients. Method We evaluated patients who received inpatient treatment for Fournier's gangrene at five hospitals in northern Germany from 1995 to 2010. Surviving patients were asked to take part in a clinical follow‐up and complete the Short‐Form 36 (SF‐36) quality‐of‐life questionnaire and a disease‐specific questionnaire including a physical examination. Results Of the 86 patients, 72 (83.7%) were men. The mean age of the patients was 57.9 ± 13.9 (25–89) years. The mean length of hospital stay was 52.0 ± 54.0 (1–329) days. Fourteen (16.3%) patients (eight men) died primarily from Fournier's gangrene. The most common aetiological event was anogenital abscess formation (n = 24; 27.9%). Seventy‐one (82.5%) patients had a mixed polymicrobial infection. SF‐36 physical role functioning (P = 0.010), physical functioning (P = 0.008), general health (P = 0.010) and physical health summary (P = 0.006) scores were significantly lower than those of the normal population. Deterioration in sexual function was reported by 65% of the patients. Conclusion Patients with Fournier's gangrene experience persistent physical and mental health problems for a long period of time following their primary hospital stay and must receive long‐term care from a variety of specialists, otherwise the disease leads to an increase in the duration of morbidity and a decrease in quality of life.